Youths' Experiences of School Re-Integration Following Psychiatric Hospitalization - Preyde, Michèle; Parekh, Shrenik; Heintzman, John (Journal of the Canadian Academy of Child and Adolescent Psychiatry, 2018)
The purpose of this study was to report youths' experiences of school re-integration post-discharge from psychiatric hospital. No reports of school reintegration from the patient perspective could be located; hence, a second objective was to explore school-related and clinical factors associated with youth who reported an unfavourable school re-integration experiences. Patients were recruited while in hospital for acute psychiatric care. They provided informed consent to be contacted post discharge regarding their perceptions of their school reintegration experience. About ten weeks after discharge youth were surveyed via telephone (n=40) or online (n=22) surveys. Of the 121 youth who agreed to be contacted after discharge, 62 youth completed the post-discharge survey. Almost half (n=29) of the youth reported that they had considerable difficulty with school reintegration. Youth reported managing social situations, academic pressures and emotions as substantial problems. Youth who reported a negative transition experience had significantly worse scores on self-reported Total and emotion subscale of the Strength and Difficulties Questionnaire, and concern about the impact of emotions on school re-entry, and significantly less psychiatrist-reported improvement than youth who reported a neutral or positive transition experience. There were no differences between the two groups on school-related variables. Youth with prior admission reported greater difficulties with peers and significantly worse clinical factors than youth without prior admissions. High emotional difficulty scores and concern about the impact of emotions on reintegration prior to discharge distinguished youths with negative school reintegration experiences. These patients may benefit from greater assistance with managing their emotional problems, and coping and social skills training before and during school reintegration.